2014
DOI: 10.1002/chem.201304461
|View full text |Cite
|
Sign up to set email alerts
|

Low‐LUMO Pyrene‐Fused Azaacenes

Abstract: A series of pyrene-fused azaacenes with four and six linearly fused rings that possess LUMO levels between -3.7 and -4.3 eV is reported. These LUMO values are remarkably lower than those typically observed for pyrene-fused azaacenes, even for systems with sixteen linearly fused rings, and are comparable to those observed for state-of-the-art n-azaacenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 66 publications
3
32
0
Order By: Relevance
“…Compounds 6 and 7 are not emissive; however, 8 emits in the red to NIR region of the electromagnetic spectrum with λ max (em)=652 nm in toluene (Table ), which is intriguing for pyrenes as they usually emit in the blue region and, to the best of our knowledge, such a red‐shifted emission has not been reported before for monomeric pyrenes. Even pyrene‐fused azaacenes reported previously do not have such a red‐shifted emission . Furthermore, compound 8 exhibits significant solvatochromism, as the emission shifts bathochromically with increasing solvent polarity from toluene to CH 2 Cl 2 by 1051 cm −1 (48 nm), confirming the CT nature of the lowest energy excited state and a significant change in dipole moment between ground state and excited state.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…Compounds 6 and 7 are not emissive; however, 8 emits in the red to NIR region of the electromagnetic spectrum with λ max (em)=652 nm in toluene (Table ), which is intriguing for pyrenes as they usually emit in the blue region and, to the best of our knowledge, such a red‐shifted emission has not been reported before for monomeric pyrenes. Even pyrene‐fused azaacenes reported previously do not have such a red‐shifted emission . Furthermore, compound 8 exhibits significant solvatochromism, as the emission shifts bathochromically with increasing solvent polarity from toluene to CH 2 Cl 2 by 1051 cm −1 (48 nm), confirming the CT nature of the lowest energy excited state and a significant change in dipole moment between ground state and excited state.…”
Section: Resultsmentioning
confidence: 68%
“…The deprotection of 5 in a trifluoroacetic acid and water mixture (6:1) is straightforward, and compound 6 was obtained in 81 % yield. The cyclocondensation reactions between dione 6 and 2,3‐diaminomaleonitrile to give 7 , or benzene‐1,2‐diamine to give 8 , were performed in an ethanol/acetic acid mixture (1:1) at 80 °C for 15 h according to the procedure of Mateo‐Alonso and co‐workers …”
Section: Resultsmentioning
confidence: 99%
“…Replacing the benzene linker by a rigid polyaromatic spacer such as pyracene [4a , 11] or pyrene12 allows related compounds in which the two azolium units are connected by a highly delocalized system to be obtained. In principle, the presence of these polyaromatic spacers introduces low‐lying LUMO levels that improve environmental stability 13. This is also important for operating electronic devices under ambient conditions, which generally requires LUMO levels located below −4.0 eV to avoid H 2 O reduction14 and to minimize O 2 trapping 15.…”
Section: Introductionmentioning
confidence: 99%
“…Mateo-Alonso et al's group [16][17][18][19] recently reported that the pyrene-fused linear acenes show enhanced stabilities. Besides, Kulisic [20] also found similar properties for pyrene-fused pyrazaacenes, a type of nitrogenated ribbonlike polycyclic aromatic hydrocarbons, with the same degree of aromaticity as acenes and a very high stability.…”
Section: Introductionmentioning
confidence: 99%